2017
DOI: 10.1007/s11103-016-0581-5
|View full text |Cite
|
Sign up to set email alerts
|

The monomeric GTPase RabA2 is required for progression and maintenance of membrane integrity of infection threads during root nodule symbiosis

Abstract: Progression of the infection canal that conducts rhizobia to the nodule primordium requires a functional Rab GTPase located in Golgi/trans-Golgi that also participate in root hair polar growth. Common bean (Phaseolus vulgaris) symbiotically associates with its partner Rhizobium etli, resulting in the formation of root nitrogen-fixing nodules. Compatible bacteria can reach cortical cells in a tightly regulated infection process, in which the specific recognition of signal molecules is a key step to select the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…The monomeric GTPase PvRabA2 is a good marker of the different developmental stages of root hairs due to its key role in root hair tip growth (S4 Fig), although it is also expressed in root tissue [53, 54]. We observed that RabA2 transcript accumulated in root hairs; as expected, the transcript accumulation was higher in zones II and III, where the cells are rapidly expanding or reaching full length, compared with zone I, where root hairs are just bulging out (S4 Fig).…”
Section: Resultsmentioning
confidence: 99%
“…The monomeric GTPase PvRabA2 is a good marker of the different developmental stages of root hairs due to its key role in root hair tip growth (S4 Fig), although it is also expressed in root tissue [53, 54]. We observed that RabA2 transcript accumulated in root hairs; as expected, the transcript accumulation was higher in zones II and III, where the cells are rapidly expanding or reaching full length, compared with zone I, where root hairs are just bulging out (S4 Fig).…”
Section: Resultsmentioning
confidence: 99%
“…They act as molecular switches during the vesicle fusion and fission to facilitate the transport of cargo molecules (Hutagalung & Novick, ) and are involved in protein recycling after endocytosis. In E. histolytica trophozoites, several authors have demonstrated that Rab‐GTPases also participate in maintaining membranes integrity and remodeling (Dalla Via et al, ; Nakayama, ). These events are fundamental for tissue invasion and phagocytosis by trophozoites (Nozaki & Nakada‐Tsukui, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, Rab-A2 members are associated with the establishment and maintenance of beneficial microbial interactions in plants (reviewed by Rivero et al, 2019). For instance, a Phaseus vulgarus Rab-A2 protein mediates polarised trafficking in the context of cell wall remodelling during colonisation by the symbiotic nitrogen-fixer Rhizobium etli (Blanco et al, 2009;Dalla Via et al, 2017). Expression of a dominant-negative Rab-A2 variant results in defects during infection thread formation, indicating that Rab-A2 is also required at later stages of infection (Dalla Via et al, 2017).…”
Section: Rab Gtpases and The Cytoskeleton In Plant Immunitymentioning
confidence: 99%
“…For instance, a Phaseus vulgarus Rab-A2 protein mediates polarised trafficking in the context of cell wall remodelling during colonisation by the symbiotic nitrogen-fixer Rhizobium etli (Blanco et al, 2009;Dalla Via et al, 2017). Expression of a dominant-negative Rab-A2 variant results in defects during infection thread formation, indicating that Rab-A2 is also required at later stages of infection (Dalla Via et al, 2017). In addition to its role in FLS2 endocytosis, RAB-A4c is also implicated in cell wall remodelling during infection with the powdery mildew Golovinomyces cichoracearum ( Fig.…”
Section: Rab Gtpases and The Cytoskeleton In Plant Immunitymentioning
confidence: 99%